Parotid gland tumour presenting in primary care: the importance of histological confirmation / Aiza Nur Izdihar Zainal-Abidin ... [et al.] - Zainal-Abidin, Aiza Nur Izdihar; Ariffin, Farnaza; Badlishah-Sham, Siti Fatimah; Mat Nor, Khariah; Geok, Chin Ta (Faculty of Medicine, 2022)
This is a report of a patient presenting to a primary care clinic with slow growing parotid gland swelling which was initially suspected as benign from ultrasound findings. A referral to the ORL (otorhinolaryngology) team was made and FNAC (Fine Needle Aspiration Cytology) results confirmed the swelling to be Acinic Cell Carcinoma. The patient subsequently underwent surgical resection. This case highlights the importance of a high clinical suspicion of malignancy in those presenting with slow growing salivary gland tumours due to its indolent nature and imaging difficulties. Histological confirmation is warranted.